Emerging evolutionary paradigms in antibiotic discovery. (1st March 2019) - Chevrette, Marc G; Currie, Cameron R
Abstract: Antibiotics revolutionized medicine and remain its cornerstone. Despite their global importance and the continuous threat of resistant pathogens, few antibiotics have been discovered in recent years. Natural products, especially the secondary metabolites of Actinobacteria, have been the traditional discovery source of antibiotics. In nature, the chemistry of antibiotic natural products is shaped by the unique evolution and ecology of their producing organisms, yet these influences remain largely unknown. Here, we highlight the ecology of antibiotics employed by microbes in defensive symbioses and review the evolutionary processes underlying the chemical diversity and activity of microbe-derived antibiotics, including the dynamics of vertical and lateral transmission of biosynthetic pathways and the evolution of efficacy, targeting specificity, and toxicity. We argue that a deeper understanding of the ecology and evolution of microbial interactions and the metabolites that mediate them will allow for an alternative, rational approach to discover new antibiotics.